Pelatihan Delapan Strategi Membangun Usaha Keluarga Masyarakat Desa Batetangnga Kabupaten Polewali Mandar - Rudi Amir; Nasrah Natsir; Marzuki, Kartini; Imran; Suwahyu, Irwansyah (Jurusan Teknik Informatika dan Komputer, 2025)
Family business is an economic entity that is controlled and inherited from generation to generation, has become an important foundation in the global economy. Rapid technological developments are very helpful in building family businesses, including in terms of finance. Digital-based financial products and services such as fintech are increasingly in demand by the public. One of the factors that drives the growth of the fintech industry is the development of SMEs. More and more SMEs are using digital services to make it easier for consumers to make transactions. The development of small and medium enterprises (SMEs) which continues to grow has also triggered the development of the fintech industry in the country. The purpose of this counseling and training is to find out how the influence of the eight-formula counseling strategy for building family businesses in Batetangnga Village, Polewali Mandar Regency. The methods used are conducting stages of observation, preparation of materials, making pre-tests and post-tests and evaluation stages. Participants in this counseling were 21 residents of Batetangnga Village. From the results of the counseling, it can be concluded that there is an increase in residents' knowledge about how to build a family business properly.